2017
DOI: 10.22159/ijpps.2017v9i7.16887
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity Evaluation of Ethanolic Extract of Aristolochia Albida Duch. Leaves on Wistar Rats Liver and Kidney Functions

Abstract: Objective: Aristolochia albida Duch is frequently used by alternative medicine to treat some pathologies like hepatitis. Our main objective was to evaluate the acute oral toxicity of the ethanolic extract of this plant.Methods: Exploratory tests for acute oral toxicity are performed in vivo on Wistar albino rats in a limit test of 2000 mg/kg for 14 d in accordance with the OECD Guidelines 423. The clinical signs were observed every day, followed by measurement of body weight change, the haematological and bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…The biochemical findings (disturbance of biochemical parameters) are confirmed by those obtained from histological examination of kidney and liver. Moreover, our results were compared to those discussed in the chronic toxicity of A. manshuriensis in which the authors reported that the absence of any significant biochemical variation after feeding mice with organic extract for eight weeks [1423]. Thus, the organic extract of A. manshuriensis was responsible for hepatic necrosis [19].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The biochemical findings (disturbance of biochemical parameters) are confirmed by those obtained from histological examination of kidney and liver. Moreover, our results were compared to those discussed in the chronic toxicity of A. manshuriensis in which the authors reported that the absence of any significant biochemical variation after feeding mice with organic extract for eight weeks [1423]. Thus, the organic extract of A. manshuriensis was responsible for hepatic necrosis [19].…”
Section: Discussionmentioning
confidence: 81%
“…The filtrate was concentrated in a rotary vacuum evaporator. The crude extract reconstituted on a daily basis in distilled water for final concentrations required for oral administration [14].…”
Section: Methodsmentioning
confidence: 99%
“…Acute oral toxicity is usually carried out in small groups of animal's gives information about the toxic profile of the plant extract. In any pharmaceutical preparation, acute oral toxicity studies are necessary to use in humans [14][15][16]. In the present study, the acute oral toxicity of ethanolic extract of A. grossus (L.f.) Goetgh.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, traditional medicine is a field that is still in a great demand for research [2]. The traditional medicine aslo safe and no toxic compared to conventional medicine [3,4].…”
Section: Introductionmentioning
confidence: 99%